Peran KPK Dalam Penegakan Hukum Tindak Pidana Korupsi di Indonesia - Putri, Dhina Yustisia Arinta (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2024)
This research discusses the role of the Corruption Eradication Commission (KPK) in improving law enforcement against criminal acts of corruption in Indonesia. The research background illustrates the escalation of corruption which is detrimental to the economy and undermines public trust in the legal system. The research methods used are policy analysis and case studies to describe the impact and effectiveness of KPK interventions. The main objective of the research is to contribute to the Corruption Eradication Commission in reducing the level of corruption, identifying obstacles to law enforcement, and providing recommendations to increase the effectiveness of this anti-corruption agency. Research findings show that the Corruption Eradication Commission has played a crucial role in tackling criminal acts of corruption, but faces significant challenges such as internal and external resistance. The research results show that the Corruption Eradication Committee has had a positive impact in eradicating corruption in Indonesia, although the challenges it faces require serious attention. Recommendations include improving regulations, strengthening inter-institutional cooperation, and increasing the KPK's internal capacity to maintain integrity and efficiency in law enforcement.